2014
DOI: 10.1039/c4ee02636e
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating different classes of porous materials for carbon capture

Abstract: We screen a wide selection of nano-porous materials with respect to CO2 capture from flue gas by employing the metric of parasitic energy designed to comprise the entire CCS process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
214
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 196 publications
(217 citation statements)
references
References 74 publications
3
214
0
Order By: Relevance
“…30,46 The CO 2 /N 2 selectivities are determined using the ideal adsorbed solution theory (IAST) 47,48 and taken from previous work. 13,32 These studies have shown that these assumptions give reasonable predictions for CO 2 /N 2 binary mixtures. The simulations in this work are performed using existing force fields.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…30,46 The CO 2 /N 2 selectivities are determined using the ideal adsorbed solution theory (IAST) 47,48 and taken from previous work. 13,32 These studies have shown that these assumptions give reasonable predictions for CO 2 /N 2 binary mixtures. The simulations in this work are performed using existing force fields.…”
Section: Methodsmentioning
confidence: 99%
“…the energy output parasitized by CCS. 32 Although the parasitic energy of some nanoporous materials is lower than for amine scrubbing, still some 20-30% of the power plant's energy output would be used for CCS, corresponding to $40-$60 per tonne of CO 2 abated. 33 Additionally, H 2 O in the exhaust stream has a detrimental effect on the performance of most nanoporous materials that have been proposed for CCS in the past, because most of the adsorption sites for CO 2 are fully saturated with H 2 O instead.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DFT calculations accounting for vdW interactions quantitatively corroborate and rationalize the observations regarding intramolecular CO 2 angles and trends in relative geometric properties and heats of adsorption in the M 2 (dobdc)-CO 2 adducts ( Table 1 ). Huck et al [ 70 ] compared the different metals in their performance for carbon capture and showed that for an ideal dry fl ue-gas mixture, the Mg version of M 2 (dobdc) performed optimally. However, Lin and co-workers [ 56 ] showed that the presence of a trace amount of water makes Mg 2 (dobdc) lose its selectivity.…”
Section: Co 2 Adsorption In the M 2 (Dobdc) Seriesmentioning
confidence: 99%
“…However, many kinds of solid adsorbents are under consideration (Wang et al, 2014a;Huck et al, 2014), based on a variety of solid substrates (Kong et al, 2015;Hao et al, 2013;Plaza et al, 2012): the potential application of the analysis is therefore broad.…”
Section: Introductionmentioning
confidence: 99%